Geology of the Metapán volcanic field NW El Salvador - Rapprich, Vladislav (2006)
Metapán volcanic field occupies the eastern margin of the Ipala Graben and represents one of several 'Behind volcanic front' type fields in El Salvador. It was subdivided into four zones in regard to the distinct age and location of each of them. The duration of the volcanic activity in the Metapán area has been from Pliocene to Quaternary. The volcanism started with the formation of the El Cóbano shield-volcano in the SE part of the study area, which is preserved as a relict of a sequence of basaltic lavas, approximately 300 m thick. Later volcanic activity represented by Strombolian cones, Hawaiian fissure vents and lava fields took place in three separated areas: El Shiste to the northwest, Ostúa to the west and San Diego to the south of the Metapán town. All studied volcanic events in this area are older than the last Plinian eruption of Ilopango caldera, which produced tephra of Tierra Blanca Joven (TBJ: 430 AD).